2016
DOI: 10.1093/conphys/cov072
|View full text |Cite
|
Sign up to set email alerts
|

Conservation physiology of animal migration

Abstract: Conservation physiology has great potential to help us understand how migratory animals interact with current and future anthropogenic threats. Migration is inherently challenging such that additional stressors derived from altered environments or interaction with human infrastructure or activities could lead to long-term changes to migratory phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 178 publications
1
80
0
Order By: Relevance
“…; Lennox et al. ). From the few studies in high (>60°N) latitude systems, temperature has been found to influence migration timing, and more research is needed on how temperature affects energy and stress levels during spawning migrations (Mundy and Evenson ; Lennox et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Lennox et al. ). From the few studies in high (>60°N) latitude systems, temperature has been found to influence migration timing, and more research is needed on how temperature affects energy and stress levels during spawning migrations (Mundy and Evenson ; Lennox et al.…”
mentioning
confidence: 99%
“…There is limited information linking variability in river conditions with energy demands of Sockeye Salmon during spawning migrations in arctic and subarctic ecosystems (Rand et al 2006;Lennox et al 2016). From the few studies in high (>60°N) latitude systems, temperature has been found to influence migration timing, and more research is needed on how temperature affects energy and stress levels during spawning migrations (Mundy and Evenson 2011;Lennox et al 2016;Carey et al 2017). Moreover, exploring the influence of river temperatures in subarctic watersheds will help generalize the impact of inriver temperature to other Sockeye Salmon populations and help managers anticipate which environmental factors will influence energetic conditions of Sockeye Salmon during spawning migrations.…”
mentioning
confidence: 99%
“…In general, migratory and high‐mobile species, like the potamodromous Iberian barbel, have a high reliance on habitat and environmental features to complete their different life‐history processes (Lennox et al, ; Lucas & Baras, ). Ultimately, at specific stages or periods of their annual and seasonal cycle (e.g., migration, growth, and reproduction), they tend to display reophilic behaviour and/or present demographic strategies particularly mediated by the timing and intensity of flow and temperature cues (Pavlov, Mikheev, Lupandin, & Skorobogatov, ; Skov et al, ), variables that are usually less important (i.e., confirmed by the poor relationships obtained in this study between chub's seasonal growth or GSI and environmental predictors) for the development of the more flexible and generalist life‐cycle strategies of resident species (Lucas & Baras, ; Tedesco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature constrains the distribution of species (Pörtner, ) and influences the timing and expression of many life history events (Walther, Post, Convey, & Menzel, ) such as breeding, aestivation/hibernation and migration (Lennox, Chapman, et al., ). For ectotherms such as most fishes, temperature directly controls, and can ultimately limit, the rates of enzymatic, metabolic and cardiac processes (Behrisch, ; Farrell, Eliason, Sandblom, & Clark, ; Fry, ).…”
Section: Introductionmentioning
confidence: 99%